(untitled) (Indian Journal of Animal Production and Management, 2024)
Temperament of dairy animal is the individual behavioural difference in response to the surrounding condition. In dairy bovines, the temperament is most important at milking because it affects efficiency of milking, milk yield and quality. Temperament negatively affects the production, reproduction, health and welfare. The temperament of dairy bovines has moderate heritability with wide variation from 0.07 to 0.53, indicates greater influence of environmental factors on this trait. Temperament shows low to moderate consistency within the individual dairy animal (repeatability = 0.04-0.56). Prepartum management interventions of dairy cattle and buffaloes particularly in primiparous animals enable them to be calmer during post-calving period which subsequently improves their production and reproduction performance, health and welfare. Therefore, management interventions particularly before calving can improve the temperament of indigenous dairy cattle and buffaloes as well as their performance.